The Importance of Innovation and Response to Consumer Preferences in Marketing Strategy - Elsa Suci Prihatini; Abel Ghandy; Iman Hilman (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Research on the marketing strategy of Toyota Innova Zenix HV highlights the importance of innovation and responding to consumer preferences. With increasing attention to fuel efficiency and environmental sustainability, companies must ensure their marketing strategies are in line with these trends. This study aims to strengthen Astra International's position in the eco-friendly vehicle market, increase sales, and support the development of the Indonesian automotive industry. The study was conducted at PT Astra International Tbk - TSO Auto2000 Yasmin, Bogor, in September-December 2023 using a qualitative method based on case studies. Primary data was obtained through interviews, while secondary data came from literature studies and internal documents. The marketing strategy analysis used the Internal-External (IE) Matrix which produced three main strategies: Growth, Stability, and Retrenchment. The SWOT analysis maps four strategies, namely SO (leveraging strengths for opportunities), ST (facing threats with strengths), WO (overcoming weaknesses with opportunities), and WT (minimizing weaknesses and threats). The strategic position of Toyota Innova Zenix HV is in quadrant I, indicating a great opportunity to implement an aggressive strategy through expansion, innovation, and investment. This holistic approach supports Auto2000 Yasmin's position in the hybrid vehicle market, while also driving sustainable growth in the long term.